If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10z + 2 = 5 Reorder the terms: 2 + 10z = 5 Solving 2 + 10z = 5 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 10z = 5 + -2 Combine like terms: 2 + -2 = 0 0 + 10z = 5 + -2 10z = 5 + -2 Combine like terms: 5 + -2 = 3 10z = 3 Divide each side by '10'. z = 0.3 Simplifying z = 0.3
| 5p+pq+6pr= | | Y=2X-40 | | -x-5*0=12 | | 36x+5(9x-x)-3x= | | 2X-40=1Y | | -0-5x=12 | | (2X-40)=Y | | 5x-91=-11 | | Logx=18.8 | | 7x-12x-5=-42+15 | | ((1/5)x^(-1/5))*(4-9x)=0 | | 0.072=1-z | | 7+-2+-4= | | 8=3.14+x | | y-21/7=x | | -8x+3(x-2)=11 | | 17=2x+6 | | 15-4x-3x^2=0 | | 2y^2+17y+31=(y+5)(y+5) | | x^2+5x+6=-x^2-3x | | -7/5y-7/2=7y-4/5 | | .75(8x-12)+5x=7-(x-30) | | 2r^2-3r=1 | | 4-.6x=3(1.5x+.9)+7.93 | | ((20/21)*((-1)^(-1/21)))-((41/21)*((-1)^(20/21))) | | 6x+16=6x-94 | | (2X-40)=X | | 2r-3r=1 | | 45/5=5x/5 | | (20/21)*(-1)^(-1/21)-(41/21)*(-1)^(20/21) | | 2K(4y-2z)+48y^2+72xy-126z^2-36xz+48y^2-12z^2=0 | | 3.7x+48.2=2.6-7.7x |